Guidelines for the Empirical Classification of Organizations - McKelvey, Bill (Administrative Science Quarterly, 1975)
Bill McKelvey After a brief review of organization classification, multivariate approaches toward the empirical identification of such classifications are discussed. Ten guidelines for conducting future multivariate classificatory studies are presented, supported by a critique of two published largescale empirical studies. Taxonomic development is viewed as a critical element in the future health of organization science.